Analysis Position of Potential Financial Distress at Bali Paragon Resort Hotel - L P Sintya Dewi; I M Sudana; N W D Ayuni (Journal of Applied Sciences in Accounting, Finance, and Tax, 2019)
The early stage of bankruptcy usually begins with financial distress. The condition of financial distress is inability of the company or unavailability of funds for payments that are due. Analysis of financial distress in the company expected to prepare a strategy to anticipate of bankruptcy. The purpose of this research is to know the position of potential financial distress at Bali Paragon Resort Hotel. This research is a quantitative research that used secondary data. The data used financial statements of Bali Paragon Resort Hotel from 2015 to 2018. The variables used is financial ratios in the Altman Z-score modification method, consists of: working capital to total assets, retained earning to total assets, earning before interest and tax to total assets, book value of equity to book value of debt. The data analysis technique used is the Altman Z-score modification method because it can be used to predict the financial condition of all types of companies. The results in this research used the Altman Z-score modification method indicate that the conditions of Bali Paragon Resort Hotel in 2015 to 2018 is non financial distress.